(untitled) - Keefe, Joseph A. (New York, 2003)
Discover your improvisational skills for a more productive, more dynamic work lifeWhether we know it or not, most of us use our improvisational skills every day in the workplace when we deal with clients and colleagues.Improv Yourself shows the reader in clear detail how to use and hone improvisational skills for better business interactions and a more productive work environment. Business expert and all-around funny guy Joe Keefe offers expert guidance on nurturing our improvisational skills to help us think on our feet, deal with customers, interact with team members, present new ideas, and brainstorm. Full of humor, wit, and expert business insight, Improv Yourself is like nothing else on the business shelf (could you tell I just made that up?).
Keywords: Creative ability in business,Organizational change,Problem solving,Risk management,Creative thinking,Sáng tạo trong kinh doanh,Giải quyết vấn đề